Stable aqueous dispersions of carbon
By using a binder-free active layer composed of high-purity CNTs and AC in the supercapacitor, the problem of energy density and power density affected by binder and graphite black in the prior art is solved, and a high-performance supercapacitor active layer is realized.
Patent Information
- Application Number
- JP2022556675
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-08-03
- Filing Date
- 2021-03-09
- Publication Date
- 2025-04-30
- Estimated Expiration
- 2041-03-09
AI Technical Summary
The energy density and power density of existing supercapacitors are limited by the presence of binding in the active layer, and when conductive graphite is used to increase conductivity, both the energy density and power density are affected.
A binder-free active layer composed of high-purity carbon nanotubes (CNTs) and activated carbon (AC) is used to form a stable carbohydrate solution in a surfactant-free aqueous solution through a high shear process, replacing the traditional combination of activated carbon and graphite black.
The high energy density and power density of the ultracapacitor are achieved, while avoiding the negative impact of the existence of the binder on performance, and supporting the thermal welding of the ultracapacitor, suitable for direct installation on printed circuit boards and electrical platforms.
Smart Images

Figure 0007670730000007 
Figure 0007670730000008 
Figure 0007670730000009
Abstract
Description
[Technical field]
[0001] The present invention relates to a stable aqueous dispersion of carbon, including activated carbon and high purity carbon nanotubes (CNTs). The aqueous dispersion is surfactant-free and stable for at least two weeks. The aqueous dispersion of carbon is useful for preparing active layers for electrodes of supercapacitors. [Background technology]
[0002] Supercapacitors are electrochemical storage devices that can bridge the gap between batteries and dielectric capacitors in terms of energy and power density. Compared to batteries, supercapacitors can deliver higher power but store less energy, and compared to capacitors, supercapacitors store more energy but deliver less power.
[0003] The ability of an electrode to hold a charge is related to the porosity of its active layer, since high porosity results in high surface area. The ability of a supercapacitor to store a charge is measured by its capacitance. The energy density of a supercapacitor is proportional to the capacitance and the square of the charging voltage. The power density of a supercapacitor is inversely proportional to its internal resistance, also called its equivalent series resistance, and proportional to the square of the charging voltage.
[0004] Activated carbon is typically used at 1,000m 2 Due to its high surface area exceeding 10000g / g, activated carbon is the most common material currently used for charge storage in capacitor electrodes. However, activated carbon is poorly conductive and cannot be coated onto a current collector foil without a binder. The binder is typically a polymer such as polyvinylidene fluoride (PVDF) and is insulating. To increase the conductivity, a conductive graphitic material such as carbon black is added to the electrode. The mixture of activated carbon, carbon black, and binder is dispersed in an organic solvent and coated onto a current collector foil, which is typically aluminum or copper. The organic solvent is then removed by drying.
[0005] Conductive carbon black particles do not exhibit significant porosity and therefore do not contribute significantly to charge storage. Therefore, both the carbon black particles and the binder are equivalent to dead volume in terms of volumetric charge capacity. Thus, the energy density of a conventional supercapacitor is reduced by the inclusion of the binder and carbon black.
[0006] Non-conductive binders increase the resistivity of the active layer of the electrode, and therefore the power density of conventional supercapacitors is reduced by the inclusion of binders. Also, binders decompose at high temperatures, so their presence in supercapacitor electrodes limits reflow soldering for direct surface mounting of supercapacitor cells onto printed circuit boards or electrical platforms. [Brief description of the drawings]
[0007] [Figure 1] FIG. 1 is a schematic diagram of an electrode. [Diagram 2] FIG. 2 shows a detailed view of the active layer of the electrode. [Diagram 3] FIG. 3 is a schematic diagram of a double-sided electrode. [Figure 4] FIG. 4 is a flow chart illustrating a method for preparing an active layer for an electrode. [Diagram 5] FIG. 5 is a schematic diagram of an exemplary mixing device. [Figure 6] FIG. 6 is a schematic diagram of a coating apparatus featuring a slot die. [Figure 7] FIG. 7 is a schematic diagram of a coating apparatus featuring a doctor blade. [Figure 8] FIG. 8 is a schematic diagram of a supercapacitor cell. [Figure 9] FIG. 9 is a schematic diagram of a packaged supercapacitor cell. [Figure 10] FIG. 10 is a photograph of the dried and calendered AC-CNT coating on the underlayer on Al foil. [Figure 11] FIG. 11 shows the Nyquist plot of an 80:20 weight (wt) % cell of AC-CNT with PC electrolyte. [Figure 12] FIG. 12 shows the Nyquist plot of an 80:20 wt % cell of AC-CNT with ACN electrolyte. [Figure 13] FIG. 13 shows the ESR and capacitance change for ≥98 wt % and <98 wt % pure CNTs in an AC-CNT 80:20 wt % cell with PC / ACN electrolyte suspended at constant voltages of 2.7 V / 2.5 V and 70° C. [Figure 14] FIG. 14 shows the ESR and capacitance change of an 80:20 wt % AC-CNT cell with PC / ACN electrolyte at 2.7 V / 2.5 V upon repeated cycling at 70° C. with 98 wt % or higher purity CNTs and with CNTs less than 98 wt % purity. [Figure 15] FIG. 15 shows the ESR and capacitance change of an 80:20 wt % AC-CNT cell with PC-DMC electrolyte at 3 V and 70° C. [Figure 16] FIG. 16 shows Nyquist plots for AC-CNT cells with ACN (top) and PC (bottom) electrolytes with no underlayer, and AC-CNT cells with two types of underlayers, one being the preferred underlayer containing sp2 carbon. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0008] The present inventors have developed stable aqueous dispersions of carbon, including activated carbon and high purity carbon nanotubes (CNTs), that are surfactant-free and stable for at least 2 weeks, at least 1 month, at least 3 months, at least 6 months, at least 1 year, or at least 2 years.
[0009] The present inventors have also developed a supercapacitor electrode having a binder-free active layer comprising a composite of activated carbon (AC) and high-purity carbon nanotubes (CNTs).
[0010] As used herein, "binder" is intended to convey the meaning of polymers, copolymers, and similar ultra-high molecular weight materials that are typically used to provide binding to carbon in the active layer of a supercapacitor electrode. Such materials are often used as binders to promote cohesion between loosely aggregated particulate materials, i.e., active filler materials that perform some useful function in a particular application. Such binders include, for example, polyvinylidene fluoride (PVDF), styrene butadiene rubber (SBR), sodium carboxymethylcellulose (CMC), and polytetrafluoroethylene (PTFE).
[0011] The supercapacitor electrodes of the present invention do not include a binder in the active layer, since it does not contribute to the charge storage capacity, and therefore it is advantageous to replace it with a material (e.g., carbon nanotubes) that can serve to store charge and maintain the integrity of the electrode. Furthermore, the absence of a binder allows cells containing the supercapacitor of the present invention to be reflow soldered for direct surface mounting onto printed circuit boards and electrical platforms.
[0012] A first aspect of the present invention relates to a supercapacitor cell having at least one electrode comprising a current collector and an active layer, the active layer comprising activated carbon and carbon nanotubes having a purity of at least 95% by weight, the active layer being free of any binder. In general, a supercapacitor cell comprises two electrodes separated by a conductive solution comprising an electrolyte.
[0013] Carbon nanotubes are high aspect ratio carbonaceous materials with large surface area and low mass density. The CNTs used in the present invention are preferably single-walled carbon nanotubes (SWCNTs), but can also include double-walled carbon nanotubes (DWCNTs) and multi-walled carbon nanotubes (MWCNTs). Depending on their chirality, single-walled CNTs (SWCNTs) are either metallic (armchair type) or semiconducting (zigzag or chiral type). The SWCNTs in the present invention can be metallic SWCNTs or semiconducting SWCNTs, or preferably a mixture of metallic and semiconducting SWCNTs. Furthermore, the CNTs are purified to such an extent that they contain less than 5% by weight of detectable metals and other impurities and have a Raman G / D integrated peak area ratio of at least 20 measured at a wavelength of 532 nm. Overall, this mixture of high purity metallic and semiconducting CNTs has a relatively high electrical conductivity.
[0014] The AC is located within the network formed by the CNTs. The binder-free active layer containing AC and CNTs exhibits more advantageous properties than the electrode active layer containing activated carbon, carbon black, and a binder. The inventors further developed a process to prepare an aqueous dispersion of AC-CNTs by a high shear process without using a surfactant.
[0015] The electrode of the present invention comprises an active AC-CNT layer that does not contain a binder. The preferred AC content in the active layer is 70-90 wt%, more preferably 75-85 wt%, and most preferably about 80 wt%. The preferred CNT content in the active layer is 10-30 wt%, more preferably 15-25 wt%, and most preferably 20 wt%.
[0016] In one embodiment, the supercapacitor electrode of the present invention reduces or eliminates the amount of non-porous conductive carbon black particles in the active layer (electrode) of the supercapacitor to achieve high energy and power density. The active electrode material contains only materials that are porous and / or conductive to increase the charge storage capacity measured by volumetric capacitance and reduce the electrode resistance, which mainly contributes to the equivalent series resistance of the cell. For example, the active electrode material (active layer) contains less than 1 wt.% carbon black or does not contain any amount of carbon black, which does not show significant porosity and does not contribute significantly to the storage of charge.
[0017] In another embodiment, depending on the particular target supercapacitor requirements, such as very low cell internal resistance, it may be desirable to include a conductive carbon black component in the electrode formulation in a minimal but sufficient amount, such as 1% to 6% by weight of the electrode.
[0018] In some embodiments, the electrode comprises an active AC-CNT layer having a thickness of 30 μm to 200 μm, more preferably 70 μm to 130 μm, and most preferably 90 μm to 110 μm. Reducing the thickness of the AC-CNT layer below 30 μm unacceptably limits the total available capacitance of the assembled cell, while increasing the thickness of the AC-CNT layer beyond 200 μm significantly limits the necessary facile diffusion of electrolyte ions in and out of the layer during charge and discharge operating cycles.
[0019] In some embodiments, the electrode includes a conductive underlayer located between the current collector and the AC-CNT active layer to reduce the interfacial resistance between the AC-CNT and the current collector. In some embodiments, the conductive underlayer has at least 20%, preferably at least 40%, or at least 50%, or at least 60%, or at least 70% sp 2A carbon layer having a mixed carbon content, preferably having a thickness of 0.01 μm to 10 μm, more preferably 0.1 μm to 5 μm, and most preferably 0.5 μm to 3 μm. In some embodiments, the conductive underlayer is a sp 2 Contains carbon and in the form of carbon nanotubes (CNTs) 2 Contains no carbon.
[0020] In some embodiments, the stable, surfactant-free aqueous AC-CNT dispersions are prepared by a high shear process.
[0021] FIG. 1 shows an electrode 100 for use in a supercapacitor of the invention. The electrode includes a current collector 102, an underlayer 104, and an active layer 106. The active layer 106 acts as an energy storage medium, for example, by providing a surface interface with an electrolyte to form an electric double layer. The underlayer 104 is optional and can be omitted if the active layer 106 exhibits good adhesion and good electrical contact to the conductive layer 102.
[0022] In some embodiments, the active layer 106 may be in the range of 30 μm to 200 μm thick. The underlayer 104 may have a thickness in the range of 0.01 μm to 10 μm.
[0023] FIG. 2 shows an active layer 106 that includes activated carbon 108 bound together by a matrix 110 of carbon nanotubes (CNTs) 112 (eg, a webbing or network formed from CNTs).
[0024] In some embodiments, the CNTs 112 forming the matrix 110 may lie primarily parallel to the major surfaces of the active layer 106, e.g., when the length of the CNTs is greater than the thickness of the active layer 106. Note that although the CNTs 112 may form straight segments, in some embodiments, e.g., when longer CNTs are used, some or all of the CNTs may instead have a curved or serpentine shape. For example, the CNTs 112 may be curved and wrapped between chunks of activated carbon 108.
[0025] In some embodiments, the length of the CNTs 112 forming the matrix 110 may range from 1 μm to 5,000 μm, or any subrange thereof, such as 5 μm to 3,000 μm, or 5 μm to 1,000 μm, or 10 μm to 1,000 μm.
[0026] In some embodiments, the CNTs 112 forming the matrix 110 have a purity of at least 95% by weight, preferably at least 97% by weight, and more preferably at least 98% by weight, and a Raman G / D integrated peak area ratio of at least 20, preferably at least 25, and more preferably at least 30, measured using a laser having a wavelength of 532 nm.
[0027] The active layer of the present invention does not include binders such as polymeric materials, adhesives, or the like.
[0028] The matrix 110 does not include any binders, but holds the activated carbon 108 together and maintains the structural integrity of the active layer 106 without peeling, delaminating, crumbling, or the like.
[0029] A matrix 110 of carbon nanotubes provides a structural framework for the active layer 106, with activated carbon 108 filling the spaces between the CNTs 112 in the matrix 110. In some embodiments, electrostatic forces (e.g., van der Waals forces) between the CNTs 112 and other carbonaceous materials 108 within the matrix 110 can provide substantially all of the bonding forces that maintain the structural integrity of the layer.
[0030] A second aspect of the present invention is directed to a stable aqueous dispersion of carbon comprising 70-90 wt. % activated carbon and 10-30 wt. % CNTs having a purity of at least 95 wt. %, wherein the dispersion is surfactant-free and stable for at least 2 weeks, at least 1 month, at least 3 months, at least 6 months, at least 1 year, or at least 2 years.
[0031] An aqueous dispersion refers to an aqueous medium containing less than 10% by weight, or less than 5% by weight, or less than 1% by weight, or less than 0.1% by weight of an organic solvent, or no organic solvent at all.
[0032] A stable dispersion is one in which no visible powder, particles, flakes, or loose aggregates settle in the solvent or to the bottom of the mixture when mechanical agitation is not applied. In a stable dispersion, the carbon does not separate from the solvent and the carbon does not settle to the bottom of the container.
[0033] In some embodiments, an aqueous suspension of AC and CNT in water is formed by adding a mixture of AC and CNT powders in a desired ratio ranging from 70:30 wt% to 90:10 wt%, more preferably 75:25 wt% to 85:15 wt%, or most preferably 80:20 wt% (AC:CNT) to a vessel containing water while introducing mechanical energy to the mixture of AC, CNT, and water in the absence of a surfactant. The preferred concentration of carbonaceous material (AC and CNT) in water is 20-40 g / liter, more preferably 25-35 g / liter, and most preferably 30 g / liter.
[0034] In some embodiments, mechanical energy is applied by stirring the mixture of AC, CNTs, and water with an impeller and / or by ultrasonic bath treatment, after which a suspension of AC and CNTs in water, i.e., an aqueous suspension of AC and CNTs, is formed.
[0035] In some embodiments, the suspension of AC and CNTs in water is exposed to a subsequent high shear process to significantly debundle the entangled strands of CNTs, after which a stable aqueous dispersion of carbon is formed.
[0036] In some embodiments, the surface area of the AC, as measured by the Brunauer-Emmett-Teller (BET) method, is less than 1,000 m 2 / g, preferably 1,200m 2 / g and more preferably 1,500m 2 / g, and the BET surface area of the CNTs is over 400 m 2 / g, preferably 600m 2 / g and more preferably 800m 2 / g.
[0037] In some embodiments, the chemical purity of the AC is greater than 95% by weight, preferably greater than 96% by weight, and more preferably greater than 98% by weight. The D50 particle size of the AC, i.e., the median particle size where 50% of the particles are larger than a given size and 50% are smaller than a given size, is preferably in the range of 1-20 μm, more preferably 3-15 μm, and most preferably 5-7 μm.
[0038] In some embodiments, the chemical purity of the CNTs is at least 95% by weight, preferably at least 97% by weight, and more preferably at least 98% by weight, and the CNTs have a Raman G / D integral peak area ratio of at least 20, preferably at least 25, and more preferably at least 30, measured using a laser with a wavelength of 532 nm. Typical impurities are iron (Fe) from the catalysis of the CNT synthesis, and chlorine (Cl) from the CNT purification process. For example, a typical level of Fe impurity is about 1% by weight, a typical level of Cl impurity is 0.5% by weight, and the remaining impurities are from other elements, such as, but not limited to, nickel (Ni) and sulfur (S).
[0039] Furthermore, because hydroxyl groups can react especially with polar solvents such as acetonitrile (ACN), the amount of hydroxyl groups on the surface of the CNTs should be minimized, i.e., the CNTs should not contain hydroxyl groups (as can be assessed by Fourier transform infrared (FTIR) spectroscopy).
[0040] The inventors have discovered that increasing the purity of the CNTs to at least 95% by weight increases the lifespan of a supercapacitor cell, as determined by an increase in cell resistance or a decrease in cell capacitance during a 1,000 hour float test at nominal cell voltage and temperature. The industry standard for a cell to pass such a test is to show less than a 100% increase in cell resistance with less than a 30% decrease in cell capacitance after 1,000 hours of float. For example, a supercapacitor cell having at least 98% by weight of purified CNTs with no hydroxyl groups in the AC-CNT active layer of the electrode and an acetonitrile electrolyte passes a life test at 2.5 V and 70° C. The same cell except with a propylene carbonate electrolyte passes a life test at 2.7 V and 70° C., and the same cell except with a polypropylene carbonate / dimethyl carbonate electrolyte passes a life test at 3.0 V and 70° C. Commercially available CNTs often have a purity of less than 85% by weight, and when they are used in supercapacitor electrodes, they experience reduced cell capacitance and increased cell failures compared to electrodes of the present invention used in supercapacitors.
[0041] The inventors have found the unexpected result that an active layer comprising AC and CNTs in a desired ratio ranging from 70:30 wt% to 90:10 wt%, preferably 75:25 wt% to 85:15 wt%, and more preferably 80:20 wt%, provides superior cell characteristics (e.g., lower resistance, higher voltage characteristics, and higher energy and power density) compared to cells having electrodes comprising AC with carbon black and a binder.
[0042] In some embodiments, the matrix 110 of CNTs 112 forms an interconnected network of highly conductive pathways for current flow through the active layer 106. For example, in some embodiments, highly conductive junctions may occur at points where the CNTs 112 of the matrix 110 cross one another or are in sufficient proximity to allow quantum tunneling of charge carriers from one CNT to the next. Although the CNTs 112 may constitute a relatively low mass fraction of the active layer (e.g., less than 25 wt%, less than 20 wt%, or less than 15 wt%), the interconnected network of highly conductive pathways formed within the matrix 110 may provide long conductive pathways (e.g., conductive pathways on the order of the thickness of the active layer 106) that facilitate the flow of current in and through the active layer 106.
[0043] As used herein, the term “highly conductive pathway” should be understood as a pathway formed by the interconnected CNTs 112 that has a higher electrical conductivity than the electrical conductivity of the activated carbon material 108 .
[0044] Without being bound by theory, in some embodiments, the matrix 110 can be characterized as an electrically interconnected network of CNTs that exhibits connectivity above a percolation threshold. The percolation threshold is a mathematical concept related to percolation theory, which is the formation of long-range connectivity in random systems. Below the threshold, so-called "giant" connected components of the order of the system size do not exist, and above the threshold, giant components of the order of the system size exist. In the matrix 110 of the present invention, which includes AC and CNTs in a specific ratio, this percolation threshold is exceeded based on the observed performance characteristics of the supercapacitor cells.
[0045] 1, in some embodiments, the conductive layer 102 may be made from a suitable conductive material, such as a metal foil. In some embodiments, the surface of the conductive layer 102 may be roughened, patterned, or otherwise textured, for example, to promote adhesion to and good electrical conductivity (i.e., low interfacial resistance) to the underlayer 104 or active layer 106. For example, in some embodiments, the conductive layer may be etched (e.g., mechanically or chemically).
[0046] In some embodiments, the conductive layer 102 may be aluminum, nickel, or copper foil.
[0047] In some embodiments, the conductive layer 102 can have a thickness in the range of 1 μm to 1,000 μm or any subrange therein, such as 5 μm to 50 μm.
[0048] In some embodiments, the underlayer 104 may be omitted such that the active layer 106 is disposed directly on the conductive layer 102 .
[0049] In some embodiments, the underlayer 104 is primarily made of sp 2 For example, in some embodiments, the underlayer 104 may comprise at least 20% by weight, preferably greater than 40% by weight, more preferably greater than 60% by weight, and most preferably greater than 70% by weight of sp 2 It may be carbon, and preferably has a thickness of 0.01 μm to 10 μm, more preferably 0.1 μm to 5 μm, and most preferably 0.5 μm to 3 μm.
[0050] In some embodiments, the underlayer 104 contains less than 10% by weight of carbon in the form of CNTs. Preferably, the underlayer 104 contains less than 5% by weight of carbon in the form of CNTs or no carbon in the form of CNTs.
[0051] In some embodiments, underlayer 104 may be formed by physical vapor deposition (sputtering), ion beam deposition, chemical vapor deposition, plasma enhanced chemical vapor deposition, spray coating, screen printing, or by coating from a slurry.
[0052] In some embodiments, the electrode 100 may be double-sided (see FIG. 3), with an underlayer 104 and an active layer 106 formed on each of two opposing major surfaces of the conductive layer 102. In some embodiments, the underlayer 104 may be omitted on one or both sides of the double-sided electrode 100.
[0053] A third aspect of the present invention relates to a method for preparing a surfactant-free aqueous dispersion of activated carbon (AC) and carbon nanotubes (CNTs), comprising the steps of mixing activated carbon and carbon nanotubes in a surfactant-free aqueous solution, the carbon nanotubes having a purity of at least 95% by weight, and dissolving the carbon nanotubes in a surfactant-free aqueous solution for at least 800,000 s -1 and subjecting the mixture to high shear at a shear rate of
[0054] The inventors have discovered that high purity CNTs (at least 95 wt%, or 97 wt%, or 99 wt%) significantly improve the stability of aqueous dispersions containing activated carbon and CNTs. The inventors have also found that the CNTs are at least 95 wt% pure, have a Raman G / D integrated peak area ratio of at least 20, and have a Raman G / D integral peak area ratio of at least 800,000 s -1 We have found that the stability of dispersions of AC (75-85 wt%) and CNT (15-25 wt%) in surfactant-free water is significantly increased, typically for at least 2 weeks, at least 1 month, at least 3 months, at least 6 months, at least 1 year, or at least 2 years, when exposed to a high shear process providing a shear rate of preferably 1,000,000 s -1 Larger, preferably 10,000,000s -1 The maximum shear rate that can be applied is 1,000,000,000 s -1Should not exceed 100,000,000s -1 should not be exceeded because exceeding this level of shear can cause unacceptable damage to the carbon.
[0055] Generally, water is the preferred solvent for preparing the active layer for environmental, economic and toxicological reasons over organic solvents such as isopropyl alcohol (IPA), methanol, ethanol, N-methyl-2-pyrrolidone (NMP), dichloromethane (DCM), dimethylsulfoxide (DMSO), dimethylcarbonate (DMC), propylene carbonate (PC), acetonitrile (ACN), etc. Stable aqueous dispersions of AC and CNTs offer substantial useful advantages compared to carbon dispersions in these organic solvents, which are harmful to the environment and human body and costly in terms of raw materials and processing. However, stable dispersions of AC and CNTs can also be prepared using IPA and NMP as solvents. In one embodiment, the stable dispersion of carbon in IPA contains 75-85 wt% activated carbon and 15-25 wt% CNTs in IPA, the purity of the CNTs is at least 95 wt%, the dispersion is surfactant-free and stable for at least 2 weeks.
[0056] In some embodiments, high shear rates can be achieved by passing the aqueous AC-CNT suspension at high velocity, e.g., 100 m / s, through one or more channels, the channels having diameters or cross-sectional dimensions of tens to hundreds of micrometers, with at least one diameter or cross-section preferably no greater than 200 μm, more preferably no greater than 150 μm, and most preferably no greater than 100 μm. For example, the aqueous AC-CNT suspension is passed through a first channel having a cross-section of 300 μm and a second channel having a cross-section of 100 μm.
[0057] The high shear process is continued until a dispersion is obtained that exhibits a viscosity suitable for the coating process. The preferred viscosity of the dispersion over the temperature range of 20-80°C is in the range of 5,000-100,000 cP, more preferably in the range of 7,000-70,000 cP, and most preferably in the range of 10,000-50,000 cP.
[0058] An exemplary embodiment of a method 200 for fabricating the active layer 106 of the electrode 100 is described with reference to FIG. 4. In step 201, AC and CNT are added to water in a desired ratio ranging from 70:30% to 90:10% by weight, preferably 75:25% to 85:15% by weight, or more preferably 80:20% by weight. The preferred concentration of carbonaceous materials (AC and CNT) in water is 20-40 g / liter, more preferably 25-35 g / liter, and most preferably 30 g / liter. In an optional subsequent step 202, an aqueous suspension of AC and CNT is formed by applying mechanical energy in the form of mixing or agitation by an impeller and / or by ultrasonic bath treatment for a period of time that ensures proper mixing of the AC and CNT in the water. For example, the impeller may be operated at 500 rpm and a torque of 60 N·cm, and the ultrasonic cleaner may be operated at 37 Hz, 100 W, and 25° C. for about 1 hour.
[0059] No surfactants or dispersants are added in either step 201 or step 202 to avoid the presence of impurities derived from these surfactants upon completion of method 200. The aqueous AC-CNT suspension typically remains in solution without settling for 1-6 hours in the absence of surfactants.
[0060] In step 203, the suspension of AC and CNTs in water is exposed to a high shear process in a high shear rotating mixer or by passing through one or more channels with diameters of tens to hundreds of micrometers to debundle the CNTs and form a stable dispersion. Aqueous AC-CNT dispersions are typically stable for at least two weeks and up to two years in the absence of surfactants.
[0061] In another embodiment of the method 200 of making the active layer 106 of the electrode 100, in the first step 211, only CNTs are added to water. The preferred CNT concentration in water is 4-8 g / L, more preferably 5-7 g / L, or 6 g / L. In the optional subsequent step 212, an aqueous suspension of CNTs is formed by applying mechanical energy in the form of mixing or stirring by an impeller and / or by ultrasonic bath treatment for a period of time sufficient to ensure good mixing of the CNTs in the water. For example, the impeller is operated at 500 rpm and a torque of 60 N·cm, and the ultrasonic cleaner is operated at 37 Hz, 100 W, and 25° C. for about 1 hour. No surfactant or dispersant is added in either step 211 or step 212 to avoid the presence of impurities derived from these substances at the completion of the method 200. The aqueous CNT suspension typically remains in solution without settling for 1-6 hours in the absence of a surfactant.
[0062] In step 213, the suspension of CNTs in water is exposed to a high shear process in a high shear rotary mixer or by passing through one or more channels having diameters of tens to hundreds of micrometers to debundle the CNTs and form a stable CNT dispersion. The aqueous CNT dispersion is typically stable for at least 2 weeks, at least 1 month, at least 3 months, at least 6 months, at least 1 year, or at least 2 years in the absence of surfactants.
[0063] In step 214, AC is then added to the CNT dispersion at a desired AC to CNT ratio ranging from 70:30 wt% to 90:10 wt%, more preferably 75:25 wt% to 85:15 wt%, or most preferably 80:20 wt%. The preferred concentration of carbonaceous materials (AC and CNT) in water is 20-40 g / liter, more preferably 25-35 g / liter, and most preferably 30 g / liter. In step 215, mechanical energy is applied in the form of mixing or agitation by an impeller and / or by ultrasonic bath treatment for a period of time that ensures proper mixing of the AC and CNT in the water. For example, the impeller is operated at 500 rpm and a torque of 60 N·cm, and the ultrasonic cleaner is operated at 37 Hz, 100 W, and 25° C. for about 1 hour. Aqueous AC-CNT dispersions, in the absence of surfactants, are typically stable for at least 2 weeks, at least 1 month, at least 3 months, at least 6 months, at least 1 year, or at least 2 years.
[0064] In step 221, the dispersion is applied by a suitable process, such as knife coating or slot die coating, to either the underlayer 104, or to the conductive layer 102 of the electrode 100 if the underlayer 104 is omitted.
[0065] In step 222, the active layer is dried by exposing the active layer 102 in the areas to be dried to an elevated temperature for a specific duration, for example 90° C. for 40 minutes, by convection heating in air or inert gas, or by infrared heating.
[0066] In step 223, the electrode 100 coated with the active layer 102 is calendered under an applied set pressure of, for example, about 23,000 psi to 235,000 psi to compress the active layer to its final thickness.
[0067] For example, an 80:20 wt % dispersion of AC:CNT is coated with a knife gap of 4 mm, dried at 90° C., and calendered under a pressure of 46,000 psi to produce an active layer with a final thickness of 100 μm.
[0068] For example, an 80:20 wt % dispersion of AC:CNT is coated with a knife gap of 6 mm, dried at 90° C., and calendered under a pressure of 46,000 psi to produce an active layer with a final thickness of 150 μm.
[0069] In a fourth aspect, the present invention relates to a method of coating a substrate, such as a current collector or a current collector primed with a carbon underlayer, the method comprising knife coating or slot die coating an aqueous dispersion onto the substrate, the dispersion comprising activated carbon and carbon nanotubes, being free of surfactants and having a viscosity in the range of 5,000-100,000 cP, and the carbon nanotubes having a purity of at least 95% by weight.
[0070] Advantageously, in some embodiments, the method 200 for forming the active layer 106 may be implemented as a roll-to-roll process (e.g., to enable mass production of electrode sheets tens of meters or longer).
[0071] FIG. 5 illustrates an exemplary apparatus 300 for fabricating the active layer 106 of the electrode 100.
[0072] Apparatus 300 includes a vessel 301. In some embodiments, the aqueous AC-CNT suspension may be initially formed in vessel 301. In other embodiments, the mixture may be formed elsewhere and then transferred to vessel 301.
[0073] In some embodiments, the vessel 301 can include an agitation mechanism, such as an impeller or another device known in the art, that operates at a controlled speed.
[0074] In some embodiments, the vessel 301 can include one or more devices for homogenization, such as a sonicator or other devices known in the art.
[0075] In some embodiments, the vessel 301 can be temperature controlled using one or more heating and / or cooling elements, such as, for example, electric heaters, tubing for circulating cold water, or any other such devices known in the art.
[0076] The aqueous AC-CNT suspension in vessel 301 is passed through flow line 302, e.g., a pipe or tube, using pump 303. Pump 303 may be of any suitable configuration, such as a peristaltic pump. A flow meter 304 may be provided to measure the rate at which the mixture flows through flow line 302. A filter 305 may be provided to filter the mixture flowing through flow line 302, e.g., to remove agglomerates of solid material having a size above a desired threshold.
[0077] In some embodiments, the aqueous AC-CNT suspension passes through one or more channels 306 having diameters or cross-sectional dimensions ranging from tens of micrometers to hundreds of micrometers, preferably having at least one diameter or cross-sectional dimension of 200 μm or less, more preferably 150 μm or less, and most preferably 100 μm or less. The CNTs in the aqueous AC-CNT mixture are debundled by exposure to high shear.
[0078] In some embodiments, a temperature control device 307, such as a heat exchanger disposed in a sleeve disposed around flow line 302, is provided to control the temperature of the aqueous AC-CNT dispersion flowing through flow line 302.
[0079] In some embodiments, a valve 308 is provided that can be selectively controlled to direct a first portion of the aqueous AC-CNT dispersion to flow through return flow line 310 for recirculation to vessel 301 and a second portion to be output externally, for example to coating apparatus 400.
[0080] In some embodiments, sensors 309, such as pressure and / or flow sensors, are provided to sense one or more sides of the output portion of the dispersion.
[0081] In various embodiments, any or all of the elements of the apparatus 300 may be operatively connected to one or more computing devices to provide automated monitoring and / or control of the mixing apparatus 300 .
[0082] In various embodiments, the coating apparatus 400 may be of any suitable type known in the art. For example, FIG. 6 shows an exemplary embodiment of the coating apparatus 400 featuring a slot die 401 that distributes the aqueous AC-CNT dispersion received from a source, such as the apparatus 300, through a distribution channel 402 onto a substrate 403 (e.g., a conductive layer 102 that is bare or already coated with an underlayer 104) moving across a roller 404. By setting the height of the slot die above the substrate 403 on the roller 404 and controlling the flow rate and / or pressure of the dispersion in the channel 402, the thickness and density of the applied coating can be controlled. In some embodiments, the channel 402 can include one or more reservoirs that help ensure a consistent flow of the aqueous AC-CNT dispersion to provide a uniform coating during operation.
[0083] Referring to FIG. 7, in various embodiments, a coating apparatus 500 features a doctor blade 501 that levels a dispersion received from a source such as apparatus 300 to be applied through one or more applicators 502 (one shown) onto a substrate 503 (e.g., a conductive layer 102, either bare or already coated with an underlayer 104) moving across a roller 504. The direction of movement of the substrate 503 is indicated by an arrow. By setting the height of the doctor blade 501 above the substrate 503 on the roller 504 and controlling the flow rate and / or pressure of the AC-CNT dispersion through the applicator 502, the thickness and density of the applied coating can be controlled. Although a single doctor blade 501 is shown, multiple blades can also be used, for example, a first blade to set the rough thickness of the coating and a second blade positioned downstream from the first blade to provide fine smoothing of the coating.
[0084] Although the above process has been described for forming an AC-CNT electrode in the absence of carbon black (CB), a small amount of CB, for example, about 1-6 wt. % CB, may be added during steps 201 or 214 of method 200 to reduce the overall equivalent series resistance (ESR) of the supercapacitor cell. For electrode formulations containing carbon black, the ratio of AC:CNT:CB is adjusted to x:yz:z wt. %, respectively. That is, the amount of CNT is reduced by the amount of CB added. For example, one embodiment of an electrode formulation includes AC:CNT:CB in a ratio of 80:15:5 wt. %. The presence of a small amount of carbon black may reduce the cell ESR, but the volumetric capacitance of a cell with AC-CNT-CB electrodes will be lower compared to a cell of the same design with AC-CNT electrodes, due to the inability of carbon black to store charge.
[0085] FIG. 8 shows an exemplary embodiment of a supercapacitor 600 (Obreja, Physica E 40 (2008), 2596-2605).
[0086] The exemplary supercapacitor 600 cell is an electric double layer capacitor (EDLC). The EDLC includes at least a pair of electrodes 603 and 604 having a pore structure 607 (wherein electrode 603 may simply be referred to as the negative electrode and electrode 604 may simply be referred to as the positive electrode for purposes of reference herein). When assembled into a supercapacitor 600, each of the electrodes 603 and 604 (each of which may be an electrode 100 of the type shown in FIG. 1) presents a double layer of charge at the electrolyte interface. In some embodiments, multiple electrodes 603 and 604 are included. However, for purposes of illustration, only one pair of electrodes 603 and 604 is shown. As a convention herein, at least one of the electrodes 603 and 604, and more typically both, includes a binder-free, surfactant-free AC-CNT active layer having a pore structure 607 (e.g., active layer 106 of electrode 100 shown in FIG. 1).
[0087] Each of the electrodes 603 and 604 includes a respective current collector 601 and 602 (also referred to as a "charge collector"), which may be the conductive layer 102 of the electrode 100 shown in FIG. 1. In some embodiments, the electrodes 603 and 604 are separated by a separator 605. Generally, the separator 605 is a thin-structured, porous, non-conductive material (usually a sheet of cellulose or polymer) used to separate the negative electrode 603 from the positive electrode 604. When assembled, the electrodes 603 and 604 and the separator 605 provide the storage cell 600.
[0088] At least one form of electrolyte 606 that conducts electricity by ionic transport is included in the supercapacitor 600. The electrolyte consists of either a salt dissolved in an aqueous or organic solvent, or an ionic liquid, which is dissociated into negative ions (anions) 609 and positive ions (cations) 611. The electrolyte 606 impregnates the pore structure 607 in the porous separator 605 and active layer, and fills the space within the electrodes 603 and 604.
[0089] In some embodiments, the electrolyte comprises about 1.8 M triethyl-methyl-ammonium-tetrafluoroborate (TEMA-BF4) dissolved in propylene carbonate (PC) of at least 99.9% purity, preferably at least 99.99% purity.
[0090] In some embodiments, the electrolyte comprises 1 M tetraethyl-ammonium-tetrafluoroborate (TEA-BF4) dissolved in acetonitrile (ACN) of at least 99.9% purity, preferably at least 99.99% purity.
[0091] In some embodiments, the electrolyte comprises 1 M tetraethyl-ammonium-tetrafluoroborate (TEA-BF4) dissolved in propionitrile (PN) of at least 99.9% purity, preferably at least 99.99% purity.
[0092] In some embodiments, the electrolyte comprises 1.5 M 5-azoniaspiro[4.4]nonane-tetrafluoroborate (SPB-BF4) dissolved in a mixture of PC and an aliphatic additive such as dimethyl carbonate (DMC) of at least 99.9% purity, preferably at least 99.99% purity.
[0093] In some embodiments, the volumes of the positive and negative electrodes are essentially the same, as determined by their respective thicknesses and areas. For example, the two electrodes are both about 100 μm thick and about 3 cm 2Since the radii of the anions and cations of the electrolyte are different, for example, the anions may be smaller than the cations, as in the case of the BF4 anion and the TEA or TEMA cation, it may be advantageous for the anode and cathode to have different volumes by varying either the thickness or area of one versus the other. For example, the capacitance of the positive electrode may be 10% greater than the capacitance of the negative electrode due to the faster diffusion of the anions versus the cations and the lower desolvation energy. In that case, a negative electrode having a volume 10% greater than the positive electrode, for example, a negative electrode that is 10% thicker or 10% greater in area, is advantageous.
[0094] When a bias voltage is applied between the two electrodes, a layer of positive charges 608 forms on the exposed pore surface of one electrode, causing attraction of negative ions 609 from the electrolyte 606, and a layer of negative charges 610 on the exposed pore surface of the other electrode causes attraction of positive ions 611 from the electrolyte 606. This results in the formation of an electric double layer on the surface of either internal electrode, resulting in high capacitance values.
[0095] In some embodiments, a supercapacitor storage cell is formed by packaging a supercapacitor cell 600 within a hermetically sealed housing 900, either as a pouch cell with generally flat electrodes, or as a cylindrical cell, or as a prismatic cell with tightly wound electrodes.
[0096] 9, the cell is hermetically sealed by welding techniques known to those skilled in the art, such as utilizing laser, ultrasonic, or other welding techniques. In addition to providing robust physical protection for the storage cell 600, the housing 900 is configured with external contacts for providing electrical communication with respective terminals 901 and 902 within the housing 900. Each of the terminals 901 and 902 in turn provides electrical access to the energy stored in the active layers of the electrodes 603 and 604, respectively, typically via electrical leads coupled to the electrodes 603 and 604, respectively.
[0097] A supercapacitor cell is rated with a nominal capacitance expressed in Farads (F) and a maximum operating voltage (V). Multiple supercapacitor cells 900 can be joined together into a bank by electrically connecting them in series, in parallel, or a combination thereof. Electrically connecting the cells in series increases the maximum operating voltage while decreasing the nominal capacitance of the pair. Electrically connecting the cells in parallel increases the nominal capacitance of the pair. For example, by electrically connecting two 1F / 2.5V cells in series, a 0.5F / 5V cell pair is provided. For example, by electrically connecting two 1F / 2.5V cells in parallel, a 2F / 2.5V cell pair is provided. For example, by electrically connecting two groups of two 1F / 2.5V cells in series and connecting the two groups in parallel, a 1F / 5V cell pair is provided. EXAMPLES
[0098] Example 1: Performance characteristics of supercapacitor cells with AC-CNT electrodes of various formulations containing purified CNTs (AC-CNT dispersion processing) For 1L of dispersion liquid, the volume is approximately 1,900m 2 24 grams of activated carbon powder having a BET surface area of 1.03 g / g was added to approximately 800 m 2 The mixture was introduced into water with 6 grams of 98 wt% or more purified CNT powder with a surface area of 1 / g and a Raman G / D integrated peak area ratio of more than 30, premixed by impeller mixing and ultrasonic bath treatment for 30 minutes, and then repeatedly passed through a 300 μm channel and an 87 μm channel connected in series three times. The aqueous dispersion product was a 30 g / L concentration AC-CNT (80:20 wt%)-water dispersion. This aqueous dispersion was stable at 20°C for at least two weeks.
[0099] (Knife-coating of AC-CNTs onto an Al current collector with a carbon underlayer) Freshly prepared aqueous AC-CNT dispersions were prepared using 100% sp 2The AC-CNT dispersions were knife-coated onto a sheet of commercial Al current collector foil primed with a carbon-containing underlayer. The knife gap was set at approximately 4.0 mm to obtain a final coating thickness of 100 μm. A total stage length of approximately 30 cm was used for knife-coating the AC-CNT dispersions. Figure 10 shows an example of a large-area AC-CNT coating produced using the knife coater across the entire stage after drying. The average time to dry one such coating using dual heat guns was 35 min. The dried AC-CNT coating had good adhesion to the underlying carbon-primed Al current collector without showing any signs of delamination. The large-area AC-CNT coating was calendered through a roll press using a pair of cover foils at a pressure of 46,000 psi and a speed of 3 m / min before vacuum oven drying at 200 °C for 16 h.
[0100] (Pouch mono cell assembly electrode) To assemble into pouch mono-cells, electrodes with dimensions 15 mm × 20 mm were punched out of various 100 μm thick AC-CNT coated aluminum strips. A 20 μm thick cellulose separator was incorporated into the pouch cells filled with either PC-based or ACN-based electrolytes. A total of 20 EDLC pouch mono-cells were assembled: 10 cells with PC electrolyte containing 1.8 M TEA-BF4 salt and 10 cells with ACN electrolyte containing 1 M TEMA-BF4 salt.
[0101] (AC-CNT cell with PC electrolyte) A cumulative plot of 10 Nyquist profiles for an EDLC pouch mono cell containing an AC-CNT 80:20 electrode and a PC-based electrolyte, shown in Figure 11, shows that there was a relatively low variation in ESR values between cells. Of note is the absence of ESR semicircle artifacts at high frequencies, indicating good adhesion of the 100 μm thick AC-CNT active layer to the carbon-primed Al current collector. The Warburg diffusion artifacts at high to mid frequencies are characteristic of thick electrodes in PC solvent. The average cell ESR value at a frequency of 1 kHz was 0.63 ± 0.02 Ω cm. 2 The average cell response time, as measured by a 45 degree phase angle between the imaginary and real parts of the impedance, is 5.0 seconds.
[0102] (AC-CNT cell with ACN electrolyte) Figure 12 shows the Nyquist profiles of the respective EDLC pouch mono cells containing an 80:20 electrode of AC-CNT and an ACN-based electrolyte. Similar to the PC-filled cells, there is no ESR semicircle artifact at high frequencies, indicating good adhesion of the 100 μm thick AC-CNT active layer to the primed Al current collector. The Warburg diffusion artifact at high to mid frequencies still persists, but is significantly smaller in magnitude compared to the same electrode in PC solvent. The average cell ESR value at a frequency of 1 kHz is 0.23 ± 0.02 Ω cm 2 The average cell response time, as measured by a 45 degree phase angle between the imaginary and real parts of the impedance, is 1.4 seconds.
[0103] Table 1 summarizes the EDLC performance characteristics of cells with AC-CNT electrodes of various formulations.
[0104] [Table 1]
[0105] Example 2: Stability of Carbon Dispersion Carbon dispersions were prepared from either 100% carbon nanotubes (CNTs) or a mixture of 20 wt% CNTs and 80 wt% activated carbon in either deionized water or isopropyl alcohol (IPA). CNTs with three different levels of purity, about 85 wt%, about 97.5 wt%, and about 99 wt%, were used to prepare the dispersions, respectively. No surfactants or other ingredients were added to the dispersions during the preparation process.
[0106] All dispersions were prepared by first combining the carbon and solvent components (water or IPA) in a container, then mixing the components with an impeller mixer operating at 500 rpm and 60 N·cm torque while simultaneously sonicating in a bath at 37 Hz, 100 w, and 25 °C for 1 h. The resulting suspension was then subjected to high shear by passing it three times through two channels in series with cross sections of 300 μm and 100 μm at a pressure of 25,000 psi. The resulting dispersions were collected in glass jars and sealed. The dispersions in the jars were observed for visual evidence of separation of the carbon from the solvent or settling of the carbon at the bottom of the container. The duration of stability was determined as the length of time during which no such settling separation was visually observed in the jar.
[0107] As shown in Table 2, dispersions prepared in aqueous solvents using CNTs with a purity of 85 wt% showed poor stability, whether prepared using only CNTs or as a mixture of AC and CNTs. In contrast, dispersions prepared in aqueous solvents using CNTs with a purity of 97 wt% or 99 wt% showed excellent stability, with no separation or settling observed after at least 6 months, whether prepared using only CNTs or as a mixture of AC and CNTs. Dispersions prepared in IPA showed comparable stability to dispersions prepared in water using CNTs with a purity of 97 wt% or 99 wt% for all CNT purity levels and compositions.
[0108] [Table 2]
[0109] Example 3: Comparison of lifetime performance data between supercapacitor cells with AC-CNT electrodes containing unpurified CNTs and supercapacitor cells with AC-CNT electrodes containing 98 wt % or more purified CNTs Aqueous surfactant-free AC-CNT dispersions with CNTs having a purity of about 85 wt% or less are not stable because the CNTs settle within a short period of time, typically within about 1 hour (see Example 2). Because suspensions of AC-CNTs containing unpurified CNTs, e.g., CNTs having a purity of about 85 wt%, do not form stable dispersions in water using the described high shear process in the absence of surfactant, AC-CNT suspensions were prepared in isopropyl alcohol (IPA) instead of water and exposed to the same high shear process.
[0110] Therefore, cells with AC-CNT active layers with high-purity CNTs formed from water-based dispersions were compared with cells with AC-CNT active layers with unpurified CNTs formed from IPA-based dispersions. Cells with PC or ACN-based electrolytes were tested by float tests at constant voltage and 100,000 constant current charge-discharge cycles for 1,000 hours.
[0111] (1000 hour floating test at 70℃) Flotation was performed by holding the cells at a fixed voltage and an elevated temperature of 70°C. The cells with PC electrolyte were floated at 2.7 V, and the cells with ACN electrolyte were floated at 2.5 V. As shown in Figure 13, the changes in both cell ESR and capacitance for the AC-CNT cells with unpurified CNTs were significantly greater than the AC-CNT cells using 98 wt% or more purified CNTs under identical test conditions. The AC-CNT cell with unpurified CNTs (85 wt% or less purity) and filled with ACN-based electrolyte (●) failed after 400 hours as its cell ESR doubled. This cell also had the greatest decay in capacitance. At the end of the 1,000-hour float test, the AC-CNT cell with unpurified CNTs and filled with PC-based electrolyte (▲) showed an 86% increase in ESR and a 22% decrease in capacitance. In contrast, both AC-CNT cells (☆ and ★), which use 98 wt % or more purified CNTs, performed significantly better than their AC-CNT (non-purified CNT) counterparts.
[0112] (100k cycle test at 70℃) The cells were cycled by repeatedly charging to 2.7 V and discharging to 0.1 V for the cells with PC electrolyte, and charging to 2.5 V and discharging to 0.1 V for the cells with ACN electrolyte while holding them at an elevated temperature of 70 °C. The changes in ESR and capacitance of both types of AC-CNT cells in PC (2.7 V) and ACN (2.5 V) during the cycling tests are shown in Figure 14. The AC-CNT cells with non-purified CNTs in PC electrolyte (▲) showed similar cycling behavior compared to the AC-CNT cells with 98 wt% or more purified CNTs in PC electrolyte (☆). However, when the filling electrolyte was ACN, the AC-CNT cells with non-purified CNTs (●) failed after only 40k cycles, showing a 105% increase in ESR and a corresponding maximum capacitance drop. This is in stark contrast to the AC-CNT pouch cell (★), with over 98 wt% purified CNTs filled with ACN-based electrolyte, which passed the 100k cycle test, showing less than a 40% increase in cell ESR and less than a 10% decay in capacitance.
[0113] Table 3 summarizes the lifetime performance comparison between cells with AC-CNT electrodes containing non-purified (np) and purified (p) CNTs.
[0114] [Table 3]
[0115] Example 4: Lifetime performance data of EDLC cells assembled from AC-CNT electrodes at high voltage A limitation of EDLC cells filled with conventional organic electrolytes PC and ACN is that they are limited to maximum operating voltages of 2.7V and 2.5V, respectively. Operating such cells for extended periods at voltages above their maximum operating voltages can cause electrochemical decomposition of the electrolyte solvent and / or salts, leading to dramatic and irreversible cell failure. The AC-CNT EDLC cells of the present invention were filled with a modified organic electrolyte consisting of a binary system of PC and aliphatic additive dimethyl carbonate (DMC) and containing 1.5M spiro salt 5-azoniaspiro[4.4]nonane-tetrafluoroborate (SPB-BF4). The floating lifetime performance of the AC-CNT cell coupled with this binary electrolyte at 3V, 70°C operation is shown in Figure 15. The cell shows only a slight increase in ESR (20%) and a negligible capacitance decrease (5%) after 1,000 hours biased at 3V.
[0116] Table 4 highlights the EDLC performance advantages of AC-CNT cells using this binary electrolyte at 3 V operation. A 25 percent gain in volumetric capacity and energy density is realized in the combined system.
[0117] [Table 4]
[0118] Example 5: High sp 2 Reduction of EDLC cell ESR using underlayer with carbon content The adhesion of the AC-CNT active layer to the underlying current collector foil was improved when deposited on a current collector with a conductive carbon primer layer compared to when deposited on an uncoated current collector foil. Furthermore, when electrodes containing AC-CNT active layers deposited on carbon-primed current collector foils were assembled into EDLC pouch cells and the performance was evaluated, the chemistry of the carbon underlayer had a significant effect on the EDLC cell ESR. Figure 16 shows the Nyquist impedance profiles of cells containing AC-CNT active layers, with PC-based or ACN-based electrolytes, and fabricated on three types of Al current collector foils. One foil type is uncoated, and the other two are coated with carbon underlayers with different carbon (C) hybridization states. The current collector foil with underlayer 1 exhibited sp 2 The foil contains more than 50% of its C in a mixed state, but has a lower layer 2, sp 3 It contains more than 65% C in a mixed state. 3 The Nyquist profile of a cell with an AC-CNT electrode fabricated on a hybrid C (C) showed an undesirable semicircle at high frequencies. Such an artifact was due to the presence of the lower layer 1 (more sp 2 Notably absent from the Nyquist profiles of cells with AC-CNT electrodes fabricated on AC-CNT active layers and high sp 2 The combination with carbon underlayer 1 showed the lowest cell ESR value (<1 Ω cm) in both PC and ACN electrolytes. 2 ) was shown.
[0119] Table 5 summarizes the ESR values of EDLC cells with AC-CNT electrodes fabricated on current collectors with no underlayer or different underlayers.
[0120] [Table 5]
[0121] Example 6: Reduction of EDLC cell ESR using AC-CNT electrodes with carbon black (CB) Table 6 summarizes the EDLC performance comparison between cells with 80:20 wt% AC-CNT electrodes and cells with 80:15 wt% AC-CNT electrodes containing 5 wt% carbon black. For EDLC cells assembled with PC-based electrolyte, the inclusion of carbon black in the electrode composition reduces the ESR by about 4% compared to cells with AC-CNT electrodes. A larger reduction in cell ESR (about 7%) is observed for ACN-based electrolyte with AC-CNT-CB electrodes. However, the reduction in cell ESR with AC-CNT-CB electrodes is accompanied by a concomitant reduction in volumetric capacitance compared to AC-CNT cells. Thus, by replacing a portion of the CNTs with CB, a high power density can be achieved while maintaining a low energy density.
[0122] [Table 6]
[0123] From the foregoing, it will be appreciated that specific embodiments of the invention have been described herein for purposes of illustration, but that various modifications may be made without deviating from the scope of the invention.
Claims
1. An aqueous dispersion comprising carbon and a water solvent, the carbon comprising 75-85 weight (wt) % activated carbon and 15-25 wt % carbon nanotubes (CNTs); the CNTs have a chemical purity of at least 95% by weight; the dispersion is free of surfactants and organic solvents; and An aqueous dispersion, wherein the carbon does not separate from the water solvent or settle to the bottom of a container for at least two weeks.
2. 10. The aqueous dispersion of claim 1, wherein the CNTs have a chemical purity of at least 97% by weight.
3. The aqueous dispersion of claim 1 , wherein the CNTs are free of hydroxyl groups.
4. 10. The aqueous dispersion of claim 1, wherein the CNTs are debundled.
5. 10. The aqueous dispersion of claim 1, wherein the CNTs have a length of at least 1 μm.
6. 2. The aqueous dispersion of claim 1, wherein the CNTs have a Raman G / D integrated peak area ratio of at least 20 measured using a laser having a wavelength of 532 nm.
7. 2. Mixing the carbon of claim 1 in a surfactant-free water solvent to form an aqueous suspension; The aqueous suspension is subjected to at least 800,000 s -1 Step of applying shear at a shear rate of 2. A method for preparing the aqueous dispersion of carbon of claim 1, comprising:
8. At least 800,000s -1 8. The method of claim 7, wherein the step of subjecting the aqueous suspension to shear at a shear rate of 0.1 to 1000 nm is accomplished by passing the aqueous suspension through at least one channel having a cross section of 300 μm or less.
9. The method of claim 7 , wherein the CNTs have a purity of at least 97% by weight.
10. The method of claim 7 , wherein the CNTs are free of hydroxyl groups.
11. The method of claim 7 , wherein the CNTs have a length of at least 1 μm.
12. 8. The method of claim 7, wherein the CNTs have a Raman G / D integrated peak area ratio of at least 20 measured using a laser having a wavelength of 532 nm.
13. 1. A method of depositing a coating on a substrate, comprising knife coating or slot die coating an aqueous dispersion onto the substrate, the dispersion comprising activated carbon and carbon nanotubes, being free of surfactants and having a viscosity in the range of 5,000 to 100,000 cP, the carbon nanotubes having a purity of at least 95% by weight, and the substrate being a current collector or a carbon-primed current collector.
14. The method of claim 13 wherein the current collector is aluminum.
15. The method of claim 13 , wherein the carbon-subcoated current collector comprises an underlayer located overlying the current collector.
16. The lower layer is sp 2 16. The method of claim 15, comprising carbon and free of CNTs.
17. 14. The method of claim 13, further comprising drying the coated substrate at about 90°C.
18. 14. The method of claim 13, further comprising calendering the coating by rolling at a pressure greater than about 23,000 psi but less than about 235,000 psi.
19. The method of claim 13, wherein the final thickness of the coating is between 30 μm and 200 μm.
Citation Information
Patent Citations
Method for producing carbon nanotube-containing composition
JP2019116398A
Composite electrode
JP2020501367A
Electrode, electric double-layer capacitor using same, and electrode manufacturing method
WO2014129540A1
Electrode structure
WO2017199884A1